Deviations from the cookie-cutter layout the actual use of space in 2-bedroom condominium units - Silvestre, Anais Marie P. (College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT Cookie-cutter layouts are provided by developers to show potential unit owners how condominium units can be used. However, apart from the developer - suggested furniture footprint plan, limited information is available regarding the features and relevance of the design of the units that the condominium developers are coming up with. The study aims to determine how actual, lived-in two-bedroom units are utilized, and if the actual usage is aligned with what developers are offering in the market. The study was exploratory in nature and utilized both quantitative and qualitative research data. A door-to-door survey composed of an interview and then actual observation of the unit was conducted, and observation forms were used to document the results. The survey was conducted in seven randomly-selected buildings from one condominium development, and yielded 85 completed surveys. Research results found numerous significant deviations from the developer- suggested furniture footprint plan- as majority of the occupants changed the suggested space layout and, used less and different furniture pieces and appliances than what was recommended. it was concluded that what developers offer may not be what the actual market needs . Several factors possibly account for the deviations of the actual furniture footprint plans from what was suggested by the developer. These may include cost implications, user anthropometrics, cultural practices, and occupant demographics and relationships. Further investigation on the effects and significance of these factors are recommended.